Central arteriovenous anastomosis for the treatment of patients with uncontrolled hypertension (the ROX CONTROL HTN study): a randomised controlled trial. Issue 9978 (25th April 2015) - Lobo, Melvin D; Sobotka, Paul A; Stanton, Alice; Cockcroft, John R; Sulke, Neil; Dolan, Eamon; van der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S; Foran, John P; Witkowski, Adam; Januszewicz, Andrzej; et al.
Summary: Background: Hypertension contributes to cardiovascular morbidity and mortality. We assessed the safety and efficacy of a central iliac arteriovenous anastomosis to alter the mechanical arterial properties and reduce blood pressure in patients with uncontrolled hypertension. Methods: We enrolled patients in this open-label, multicentre, prospective, randomised, controlled trial between October, 2012, and April, 2014. Eligible patients had baseline office systolic blood pressure of 140 mm Hg or higher and average daytime ambulatory blood pressure of 135 mm Hg or higher systolic and 85 mm Hg or higher diastolic despite antihypertensive treatment. Patients were randomly allocated in a 1:1 ratio to undergo implantation of an arteriovenous coupler device plus current pharmaceutical treatment or to maintain current treatment alone (control). The primary endpoint was mean change from baseline in office and 24 h ambulatory systolic blood pressure at 6 months. Analysis was by modified intention to treat (all patients remaining in follow-up at 6 months). This trial is registered with ClinicalTrials.gov, number NCT01642498 . Findings: 83 (43%) of 195 patients screened were assigned arteriovenous coupler therapy (n=44) or normal care (n=39). Mean office systolic blood pressure reduced by 26·9 (SD 23·9) mm Hg in the arteriovenous coupler group (p<0·0001) and by 3·7 (21·2) mm Hg in the control group (p=0·31). Mean systolic 24 h ambulatory blood pressure reduced by 13·5 (18·8) mm Hg (p<0·0001) in arteriovenous coupler recipients and by 0·5 (15·8) mm Hg (p=0·86) in controls. Implantation of the arteriovenous coupler was associated with late ipsilateral venous stenosis in 12 (29%) of 42 patients and was treatable with venoplasty or stenting. Interpretation: Arteriovenous anastomosis was associated with significantly reduced blood pressure and hypertensive complications. This approach might be a useful adjunctive therapy for patients with uncontrolled hypertension. Funding: ROX Medical.